국내 화학사고 데이터와 영국 HCRD 비교 분석 연구 - 김다희; 이창준; 정승호 (한국위험물학회지, 2023)
In this study, we tried to analyze and compare chemical accident data to suggest measures to prevent chemical accidents and improve safety management. The chemical accident database provided by the Korea Chemical Safety Agency and the Hydrocarbon Release Database (HCRD) provided in the UK were summarized, and the two databases were used to analyze the current status of accidents such as month, time, size and various causes of accidents. The analysis showed that the two countries had a common point of increased frequency of accidents in summer and at 10-12 o’clock and that the domestic cause of accidents was the ratio of human causes, and that the UK had a large ratio of physical causes. Through this, a safety management plan for the cause and frequency of accidents was presented in this study, and if the results of this study are applied, it is judged that the occurrence of chemical accidents will be reduced.
Keywords: accident database; accident analysis and comparison; HCRD